Graphene quantum dots as universal fluorophores and their use in revealing regulated trafficking of insulin receptors in adipocytes - Zheng, Xin Ting (2013)
Graphene quantum dots (GQDs) hold great promise as a new class of fluorophores for bioimaging, owing to their remarkable physicochemical properties including tunable photoluminescence, excellent photostability, and biocompatibility. Despite their highly anticipated potentials, GQDs have yet to be used to specifically label and track molecular targets involved in dynamic cellular processes in live cells. Here, we demonstrate that GQDs can serve as universal fluorophores for bioimaging because they can be readily conjugated with a wide range of biomolecules while preserving their functionalities. As a proof-of-concept demonstration, insulin-conjugated GQDs have been synthesized and utilized for specific labeling and dynamic tracking of insulin receptors in 3T3-L1 adipocytes. Our experiments reveal, for the first time, that the internalization and recycling of insulin receptors in adipocytes are oppositely regulated by apelin and TNFα, which may contribute to the regulations of these two cytokines in insulin sensitivity.